European Unemployment Revisited: Shocks, Institutions, Integration - Giuseppe Bertola (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper painstakingly restores a vintage empirical model of unemployment determination by interacting shocks and institutions, and runs it on recent data featuring dramatic shocks and controversial institutional change. Theoretical insights and empirical results suggest that reforms and capital flows contribute sensible and interrelated explanations for the recent twists and turns of unemployment rates in Europe and elsewhere.
Keywords: E24; 330